Spatiotemporal distribution characteristics of Nanjing place names—Based on data mining of Tang-Song poetry and online travelogues - Weiya Zhang; Zhicheng Lai; Shu Tang (PLoS ONE, 2025)
Tang-Song poetry, a distinguished element of China’s traditional cultural heritage, is intricately linked with the historical and cultural development of Chinese cities. This paper uses Nanjing as a case study and applies digital humanities techniques to analyze and compare the spatiotemporal distribution of place names found in Tang-Song poetry with those in online travel narratives. The aim is to uncover key factors that have influenced the cultural continuity of these historical cities and their relevance today. Findings indicate that: (1) Locations mentioned in Tang and Song poetry show significant spatial differentiation, with urban areas displaying a clustered distribution and suburbs showing scattered hotspots. (2) The number of locations referenced in Song poetry increased significantly compared to Tang poetry, suggesting that Nanjing’s economic growth heightened the city’s appeal and inspired more literary output. (3) Song Dynasty poetry reflects a shift toward more neutral and negative emotions, with a marked decrease in positive expressions. This rise in negative sentiment can be traced to the decline in national strength from the Tang to the Song Dynasty, amplifying Nanjing’s role as a place of reflection and mourning. (4) Nanjing’s cultural hotspots, such as Xuanwu Lake and the Zhongshan Scenic Area, feature prominently in both Tang-Song poetry and modern travelogues. This study contributes to research in literary geography and literary tourism at the urban spatial level, offering fresh insights into the cultural legacy of historical cities.